1999
DOI: 10.1002/(sici)1099-1409(199906)3:5<331::aid-jpp138>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

The Electronic and Non-linear Optical Properties of Oxo-titanium Phthalocyanines

Abstract: The valence electronic properties of some unsubstituted and peripherally substituted oxo-titanium phthalocyanines are reported. Semiempirical quantum chemical calculations show that the nature of peripheral substituents has a strong bearing on the valence electronic properties, including the state dipole moments and absorption wavelength. The non-linear optical response was measured around the the Q-band resonance. The effect of different substituents and substitution patterns on the non-linear behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
41
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 18 publications
1
41
0
Order By: Relevance
“…[1Ϫ6] Previously we have shown that the presence of substituents at the periphery of phthalocyaninatotitanium oxides alters the electronic distribution of the ring as seen by the energy shift of some optical transitions, [7] and modifies drastically the molecular packing of the phthalocyanine in the solid state with relevant consequences for the electronic transport properties. [6,8,9] Another motive of interest in the preparation of PcTiO, R x PcTiO, and related compounds relies upon the possibility of creating materials with remarkable nonlinear optical (NLO) properties.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…[1Ϫ6] Previously we have shown that the presence of substituents at the periphery of phthalocyaninatotitanium oxides alters the electronic distribution of the ring as seen by the energy shift of some optical transitions, [7] and modifies drastically the molecular packing of the phthalocyanine in the solid state with relevant consequences for the electronic transport properties. [6,8,9] Another motive of interest in the preparation of PcTiO, R x PcTiO, and related compounds relies upon the possibility of creating materials with remarkable nonlinear optical (NLO) properties.…”
Section: Introductionmentioning
confidence: 96%
“…[6,8,9] Another motive of interest in the preparation of PcTiO, R x PcTiO, and related compounds relies upon the possibility of creating materials with remarkable nonlinear optical (NLO) properties. [10Ϫ15] In fact, PcTiO, [14] R x PcTiO, [7] and analogous phthalocyanines [10,15] have some of the highest values of the third-order optical susceptibility χ (3) among organic chromophores. [13,15] The reasons for this must be found in the presence of a large network of conjugated π-electrons, which confers high electrical polarizability to the Pc ring and offers the possibility of several kinds of electronic transitions in the UV/Vis spectral range.…”
Section: Introductionmentioning
confidence: 99%
“…The periphery of such macrocycles can be diversified by substitution with various groups which enable enhanced solubility in common organic solvents and which impart changes to the electronic properties of the Pc ring [14]. The presence of various positional isomers in tetra-substituted derivatives has been shown to account for their higher solubility versus their octa-substituted counterparts [15].…”
Section: Introductionmentioning
confidence: 99%
“…Our aim was to synthesize a variety of new axially substituted titanium(IV) phthalocyanines and to compare their properties with the well-known PcTiO and R x PcTiO, e.g. concerning their photoconductive and non-linear optical properties [11,12].…”
Section: Introductionmentioning
confidence: 99%